Exploring the impact of social media utilization on perceived information overload: the mediating role of information disorder experiences - Masrek, Mohamad Noorman; Baharuddin, Mohammad Fazli; Heriyanto (Faculty of Information Management, 2025)
Social media platforms provide numerous benefits, such as global connectivity and rapid information sharing, but they also pose significant challenges, including managing interactions and assessing content reliability. Many users report feeling overwhelmed by excessive information and uncertainty regarding its accuracy. This study explores three research questions: (i) How does social media utilization influence perceived information disorder experience? (ii) How does social media utilization influence perceived information overload? and (iii) To what extent does perceived information disorder experience mediate the relationship between social media utilization and information overload? Using an online questionnaire, data were collected from Malaysian internet users to measure key constructs. The findings reveal that social media utilization is positively associated with perceived information disorder experience. However, the direct link between social media utilization and information overload was not significant. Importantly, perceived information disorder experience mediates this relationship. These findings have practical implications for social media designers, policymakers, and educators. Designers should address algorithmic biases that prioritize engagement over content accuracy, reducing exposure to disinformation. Policymakers can advocate for stricter content moderation regulations and tools for identifying unreliable information. Educators can enhance media literacy programs, equipping users to critically evaluate information and mitigate the negative effects of information disorder and overload.